Structure of Flow Fields Downstream of Two Different Swirll Generators - Štefan, David; Rudolf, Pavel (My University, 2012)
This paper discusses the comparison of the flow fields downstream of two different swirl generators. Both swirl generators are used to imitate the flow at the exit of the hydraulic turbine runner and study spatio-temporal behaviour of the swirling flow in the draft tube (i.e. outlet diffuser part of the hydraulic turbine), which undergoes breakdown into vortex rope. Unsteady CFD computations are carried out for identical Reynolds number. Resulting velocity and vorticity profiles are correlated with the structure of the vortex rope. Difference in excited pressure pulsations is illustrated on amplitudefrequency spectra of static wall pressure.

This paper discusses the comparison of the flow fields downstream of two different swirl generators. Both swirl generators are used to imitate the flow at the exit of the hydraulic turbine runner and study spatio-temporal behaviour of the swirling flow in the draft tube (i.e. outlet diffuser part of the hydraulic turbine), which undergoes breakdown into vortex rope. Unsteady CFD computations are carried out for identical Reynolds number. Resulting velocity and vorticity profiles are correlated with the structure of the vortex rope. Difference in excited pressure pulsations is illustrated on amplitudefrequency spectra of static wall pressure.
Structure of Flow Fields Downstream of Two Different Swirll Generators
Keywords: swirl generator; vortex rope; velocity profile; vorticity; pressure fluctuations.; swirl generator; vortex rope; velocity profile; vorticity; pressure fluctuations.